Influence of classroom climate on socio-emotional well- being of students with hearing impairment in Ibadan, Oyo State, Nigeria (2015)
This study examined the influence of classroom climate on socio-emotional well-being of students with hearing impairment in Ibadan, Oyo state in Nigeria, Descriptive survey research design of correlational type was used to carry out the study. Sample consisted of 231 students with hearing impairment using purposive sampling technique, from three schools in Ibadan, Oyo state, Nigeria. Two standardized instruments were used to collect data - My Class Inventory ( r=0.78) and Students Socio-emotional well-being Scale (r=0.82). Three research questions were answered and data were analyzed using Pearson Product Moment Correlation and Multiple Regression analysis. The results indicated that student- students interactions (r=0.62, p<0.05) and communication (r=0.54, p<0.05) significantly correlated with socio-emotional well-being of students with hearing impairment. Student- teacher interactions and discipline in the classroom did not correlated with socio-emotional well-being of students with hearing impairment. However, students-teacher interactions, student-student, interaction communication and discipline in the classroom predicted socio-emotional well-being of students with hearing impairment F(4, 208)= 1013.66) P< 0.05, while the relative contributions of independent variables to the dependent variable are as follows: students-students- interaction (β = 0357), communication (β =0.218), discipline in the classroom (β=0.357) and student-teacher interaction (β =0.031) respectively. It is therefore recommended that teachers should ensure good classroom climate in order to boost the socio-emotional development of students with hearing impairment.